2017
DOI: 10.1002/jmv.24755
|View full text |Cite
|
Sign up to set email alerts
|

Combinations of 1,8‐cineol and oseltamivir for the treatment of influenza virus A (H3N2) infection in mice

Abstract: It is need for development of new means against influenza virus due to the lack of efficacy of available therapeutic strategies. In previous research, 1,8-cineol exert its inhibition of nuclear factor (NF)-κB, the main regulator of cytokine and chemokine production in influenza, and anti-inflammatory activity. These fact supports and helps establish the hypothesis that 1,8-cineol may have synergism with an antiviral on influenza virus infection. The combined effect of 1,8-cineol with oseltamivir in a mouse typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…showed that combined treatment with baricitinib, a selective inhibitor of Janus kinase and remdesivir (an inhibitor of viral, RNA-dependent RNA polymerase) had a greater impact than remdesivir alone in reducing recovery time and improving clinical status of patients hospitalized with COVID-19 ( 59 ). Similarly, different combined-treatment approaches, at least in mouse models, have been reported as promising therapeutic options against influenza pneumonia, namely, hepatocyte growth factor and oseltamivir ( 60 ), clopidogrel (platelet receptor antagonist) and oseltamivir ( 61 ), 1,8-cineol and oseltamivir ( 62 ), L-N G -monomethyl-arginine and oseltamivir ( 63 ), and sphingosine-1-phosphate receptor agonist and oseltamivir ( 64 ). However, translation of these animal studies into clinical practice is limited, as treatments in these studies were commenced either on the day of viral infection or before the onset of clinical signs.…”
Section: Discussionmentioning
confidence: 99%
“…showed that combined treatment with baricitinib, a selective inhibitor of Janus kinase and remdesivir (an inhibitor of viral, RNA-dependent RNA polymerase) had a greater impact than remdesivir alone in reducing recovery time and improving clinical status of patients hospitalized with COVID-19 ( 59 ). Similarly, different combined-treatment approaches, at least in mouse models, have been reported as promising therapeutic options against influenza pneumonia, namely, hepatocyte growth factor and oseltamivir ( 60 ), clopidogrel (platelet receptor antagonist) and oseltamivir ( 61 ), 1,8-cineol and oseltamivir ( 62 ), L-N G -monomethyl-arginine and oseltamivir ( 63 ), and sphingosine-1-phosphate receptor agonist and oseltamivir ( 64 ). However, translation of these animal studies into clinical practice is limited, as treatments in these studies were commenced either on the day of viral infection or before the onset of clinical signs.…”
Section: Discussionmentioning
confidence: 99%
“…Antinociceptive[223]f. Antiviral[224]Rosmanola. Antinociceptive, antidepressant, and anxiolytic[82]b.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the combination of EOs might be a good strategy for fighting coronaviruses as they are more effective against foodborne pathogens and spoilage bacteria [94,95]. EO ingredients may act synergistically to enhance the effects of other antiviral drugs, or they may relieve COVID-19 symptoms [96], e.g., 1., combinations of eucalyptol and oseltamivir increased the number of survivors, improved lung parameters (viral titers, lung index, and pathology) and reduced cytokines (IL-1β, IL-10, TNF-α) expression in the lung [97], e.g., 2., the combination of Melissa officinalis EO and oseltamivir enhanced the effect of oseltamivir against avian influenza A virus (H9N2) [98], e.g., 3., germacrone plus oseltamivir exhibited additive anti-influenza virus effects in both in vivo and in vitro [99], and, e.g., 4., piperitenone oxide (the main component of Mentha suaveolens EO) plus acyclovir also exhibited synergistic activity against HSV1 [15].…”
Section: Advantages Of Essential Oils As Antiviral Drugsmentioning
confidence: 99%